Let Food Be Thy Medicine: Diet, Nutrition, and Biomarkers’ Risk of Alzheimer’s Disease - Mosconi, Lisa (Curr Nutr Rep, 2015)
Epidemiological evidence linking diet—one of the most important modifiable lifestyle factors—and risk of Alzheimer’s disease (AD)—the most common cause of dementia—is rapidly increasing. However, the biological mechanisms underlying the relationship between dietary nutrients, brain aging, and risk of AD are largely unexplored. Recent studies using brain imaging and biological markers of AD have begun to clarify how diet and nutrition modulate risk of AD in cognitively normal individuals, especially those at increased genetic risk. Such knowledge is critical prior to implementing dietary recommendations for prevention and treatment of disease.